Associations Between Dietary Added Sugars, Glycemia, and BMI (P21-066-19). (13th June 2019) - Sharpe, Kassidy; Mikati, Hala El; Pike, Julie; Smith, Lisa; Boushey, Carol; Zhu, Fengqing; Delp, Edward; Hannon, Tamara; Gletsu-Miller, Nana
Abstract: Objectives: American adolescents have a nutrient-poor diet pattern, which is particularly high in added sugars, putting them at risk for obesity and type 2 diabetes (T2D). We aimed to assess dietary intake of added sugars in adolescents and relationships with glycemia and body mass index (BMI). Methods: Cross-sectional, baseline measures were obtained from an ongoing, randomized controlled behavioral intervention to prevent adolescent T2D. Participants, using the Technology Assisted Dietary Assessment system (TADA), created a mobile, imaged-based, four-day food record which the Nutrition Data System for Research (NDSR, University of Minnesota, Minneapolis, MN) analyzed. Glucose dynamics were measured at fasting and during an oral glucose tolerance test (OGTT), using point of care instruments (DCA Analyzer, Siemens Medical Solutions, Malvern, PA; YSI Analyzers, Xylem Inc., Yellow Springs, OH). High added sugar intake was defined as consuming above the recommendation of 10% of calories from the US Dietary Guidelines. Independent sample T-tests assessed the differences between groups consuming high versus recommended amounts of added sugars. Values are expressed as mean ± standard deviation. Results: Thirty-one adolescents, ages 15.5 ± 2.4 years, were screened. The sample was composed of 12 boys and 19 girls, and 45% had prediabetes. The BMI of the sample was 34.3 ± 6.8 kg/m 2 with no differences between normal status and prediabetes groups. Similarly, normal status (11.2 ± 4.6%) and prediabetes (11.3 ± 5.0%) groups each consumed excess amounts of added sugars with no differences between groups. There were no significant differences between glycated hemoglobin (HbA1c, 5.5 ± 0.5% and 5.3 ± 0.2%), 2 hour glucose concentrations (125.4 ± 28.7 mg/dL and 111.9 ± 22.0 mg/dL), or BMI (33.9 ± 6.0 kg/m 2 and 34.9 ± 8.2 kg/m 2 ) between the groups with high versus recommended intakes of added sugar, respectively. The fasting plasma glucose concentrations in the group with high intakes of added sugar tended to be higher compared to the group with recommended intake of added sugar (94.6 ± 5.7 mg/dL versus 90.8 ± 5.1 mg/dL, P = 0.095). Conclusions: Fasting glucose may be higher in adolescents consuming excess compared to recommended amounts of added sugars. This research highlights the need for additional research to clarify the metabolic consequences of high amounts of added sugars in the diets of adolescents with obesity and a risk for developing type 2 diabetes. Funding Sources: McKinley Foundation, Indiana CTSI Project Development Team UL1TR002529.